Adventitious Rooting in Populus Species: Update and Perspectives - Bannoud, Florencia; Bellini, Catherine (Frontiers in Plant Science, 2021)
Populus spp. are among the most economically important species worldwide. These trees are used not only for wood and fiber production, but also in the rehabilitation of degraded lands. Since they are clonally propagated, the ability of stem cuttings to form adventitious roots is a critical point for plant establishment and survival in the field, and consequently for the forest industry. Adventitious rooting in different Populus clones has been an agronomic trait targeted in breeding programs for many years, and many factors have been identified that affect this quantitative trait. A huge variation in the rooting capacity has been observed among the species in the Populus genus, and the responses to some of the factors affecting this trait have been shown to be genotype-dependent. This review analyses similarities and differences between results obtained from studies examining the role of internal and external factors affecting rooting of Populus species cuttings. Since rooting is the most important requirement for stand establishment in clonally propagated species, understanding the physiological and genetic mechanisms that promote this trait is essential for successful commercial deployment.